The depletion attraction: an underappreciated force driving cellular organization - Marenduzzo, D; Finan, K; Cook, P (Rockefeller University Press, 2006)
Cellular structures are shaped by hydrogen and ionic bonds, plus van der Waals and hydrophobic forces. In cells crowded with macromolecules, a little-known and distinct force - the "depletion attraction" - also acts. We review evidence that this force assists in the assembly of a wide range of cellular structures, ranging from the cytoskeleton to chromatin loops and whole chromosomes.